Potentilla reptans L. postconditioning protects reperfusion injury via the RISK/SAFE pathways in an isolated rat heart - Ayesheh Enayati; Aref Salehi; Mostafa Alilou; Hermann Stuppner; Mirali Polshekan; Maryam Rajaei; Mona Pourabouk; Ali Jabbari; Zohreh Mazaheri; Narguess Yassa; Hamid Reza Moheimani; Vahid Khori (BMC, 2021)
Abstract Background Our previous study indicated that Potentilla reptans root has a preconditioning effect by its antioxidant and anti-apoptotic effects in an isolated rat heart ischemia/reperfusion (IR) model. In the present study, we investigated the post-conditioning cardio-protective effects of Potentilla reptans and its active substances. Methods The ethyl acetate fraction of P. reptans root (Et) was subjected to an IR model under 30 min of ischemia and 100 min of reperfusion. To investigate the postconditioning effect, Et was perfused for 15 min at the early phase of reperfusion. RISK/SAFE pathway inhibitors, 5HD and L-NAME, were applied individually 10 min before the ischemia, either alone or in combination with Et during the early reperfusion phase. The hemodynamic factors and ventricular arrhythmia were calculated during the reperfusion. Oxidative stress, apoptosis markers, GSK-3β and SGK1 proteins were assessed at the end of experiments. Results Et postconditioning (Etpost) significantly reduced the infarct size, arrhythmia score, ventricular fibrillation incidence, and enhanced the hemodynamic parameters by decreasing the MDA level and increasing expression of Nrf2, SOD and CAT activities. Meanwhile, Etpost increased the BCl-2/BAX ratio and decreased Caspase-3 expression. The cardioprotective effect of Etpost was abrogated by L-NAME, Wortmannin (a PI3K/Akt inhibitor), and AG490 (a JAK/STAT3 inhibitor). Finally, Etpost reduced the expression of GSK-3β and SGK1 proteins pertaining to the IR group. Conclusion P. reptans reveals the post-conditioning effects via the Nrf2 pathway, NO release, and the RISK/SAFE pathway. Also, Etpost decreased apoptotic indexes by inhibiting GSK-3β and SGK1 expressions. Hence, our data suggest that Etpost can be a suitable natural candidate to protect cardiomyocytes during reperfusion injury.